2012
DOI: 10.1111/eth.12006
|View full text |Cite
|
Sign up to set email alerts
|

Flight Initiation Distance and Starting Distance: Biological Effect or Mathematical Artefact?

Abstract: In many studies, flight initiation distance (FID, the distance at which a prey starts to flee at the approach of a walker) is positively related to starting distance (SD, the distance at which the walker begins to approach) and alert distance (AD, the distance at which the focal individual becomes alert to the threat). In spite of the fundamental differences between SD, a covariate that may not have any biological effect, and AD, a measure related to the behaviour of the animal, it is common to use SD as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 47 publications
3
75
1
Order By: Relevance
“…Recently, it has been suggested that the relationship between FID and SD is a mathematical artefact and that it has no biological relevance (Dumont et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that the relationship between FID and SD is a mathematical artefact and that it has no biological relevance (Dumont et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; but see Cooper and Dumont et al. ). This relationship is thought to result from the increasing costs of monitoring incoming predators for an extended period of time (Blumstein ) although other explanations exist (Weston et al.…”
mentioning
confidence: 98%
“…Flight response to a stimulus is frequently relied upon in wildlife studies and can be recorded in a variety of ways (Miller, Garner, & Mench, ). Flight initiation distance (FID), the distance at which an animal flees from an approaching stimulus, is highly correlated with alert distance (AD), the distance at which prey become aware of the stimulus, and the distance from which the stimulus approach commenced (Dall, Houston, & McNamara, ; Dumont, Pasquaretta, Réale, Bogliani, & Hardenberg, ). Alert behaviors can be difficult to identify in some species as there may be no clear indicators of stimulus detection.…”
Section: Methodsmentioning
confidence: 99%
“…Flight initiation distance (FID), the distance F I G U R E 1 Location of study area within New South Wales, Australia, showing roads and forested and cleared areas within the study area. Property boundaries and human disturbance were omitted to ensure anonymity at which an animal flees from an approaching stimulus, is highly correlated with alert distance (AD), the distance at which prey become aware of the stimulus, and the distance from which the stimulus approach commenced (Dall, Houston, & McNamara, 2004;Dumont, Pasquaretta, Réale, Bogliani, & Hardenberg, 2012). Alert behaviors can be difficult to identify in some species as there may be no clear indicators of stimulus detection.…”
Section: Behavioral Responsesmentioning
confidence: 99%
“…Given the lack of information for the taxon, we addressed the effects of ontogeny on SD as it has been found to be controversially important in the study of escape behavior (Cooper, 2005;Dumont et al, 2012;Samia et al, 2013) and is a foundational element to the advanced study of SD influence on FID. Supporting our previous finding (Hayes et al, in press),…”
Section: The Differential Pattern We Observed In Oregon Spotted Frogsmentioning
confidence: 99%